The effect of Vocaroo as media in teaching students' dental fricative pronunciation - Mahendra, Nasrul Rija (Indonesian Journal of Curriculum and Educational Technology Studies, 2023)
This study investigates the integration of Vocaroo to enhance seventh-grade students' dental fricative pronunciation in descriptive texts. Using a pre-experimental one-group pre and post-test design, 30 students from SMPN 9 Pontianak were selected through cluster-random sampling. Data collected via pre and post-tests underwent rigorous statistical analysis, demonstrating that Vocaroo was effective in fricative articulation instruction. Statistical evidence, notably the t-test (11.037 > 2.045), supports this finding, with 29 degrees of freedom at a significance level of 0.05. Hypothesis Ha was accepted, and null hypothesis Ho was rejected as the t-test surpassed the critical value. The treatment's effect size, 1.88, highlights its pedagogical impact. Vocaroo emerges as an effective medium with a strong effect, and teachers recommend it for dental fricative pronunciation exercises. Abstrak Penelitian ini menyelidiki integrasi Vocaroo untuk meningkatkan kemampuan pelafalan fricative dental siswa kelas tujuh dalam teks deskriptif. Dengan menggunakan desain pra-eksperimental pre dan post-test satu kelompok, 30 siswa SMPN 9 Pontianak dipilih secara acak kluster. Data yang terkumpul melalui pre dan post-test mengalami analisis statistik yang ketat, menunjukkan Vocaroo efektif dalam instruksi pelafalan fricative. Bukti statistik, terutama uji-t (11,037 > 2,045), mendukung temuan ini, dengan 29 derajat kebebasan pada tingkat signifikansi 0,05. Hipotesis Ha diterima, hipotesis nol Ho ditolak karena nilai uji-t melampaui nilai kritis. Besar efek perlakuan, 1,88, menyoroti dampak pedagogisnya. Vocaroo adalah medium yang efektif dengan efek yang kuat yang direkomendasikan kepada guru untuk latihan pelafalan fricative dental.